Hylarana erythraea voice call character (Schlegel, 1837) in Campus Area Universitas Negeri Padang - Nandia Nandia; Fitra Arya Dwi Nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
The types of anura that are very widely distributed are predicted to consist of several species, such as the Hylarana erythraea species. Although common and widespread, research to reveal the character of this type of call sound has not been carried out. This study aims to analyze the character of the voice called H. erythraea from the Padang State University campus area. A total of 27 calls were successfully recorded and then analyzed using RavenPro 1.6.1 software. The results show that H. erythraea has two types of calls. Type 1 consists of two notes, while type two only consists of one note. Call frequency in both types is not modulated. The average call duration for type one is 0.45 seconds, while for type two is 0.056 seconds. The average dominant frequency of type one calls is 1894.92 Hz and type two is 1860.47 Hz. The average call interval is 5.16 seconds. The mean dominant frequency or call duration of the West Sumatran sample differs from that of the Singaporean and Thai populations. Further confirmation using more comprehensive evidence is expected to confirm the taxonomic status of H. erythraea of the entire distribution area.